Ione Getscher letter to Nicholas S. Halmi regarding spring bird sightings, May 16, 1979 - Getscher, Ioneet al (1979)
Letter from Ione Getscher to Nicholas S. Halmi regarding spring bird sightings, May 16, 1979. Sightings of Merlin and Glaucous Gull are underlined in red. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed